PELATIHAN MANAJEMEN KEUANGAN DAN AKUNTANSI UNTUK UNIT JASA EKSTRAKURIKULER SEKOLAH SMKS MUSIK JAKARTA - Erliana, Erliana; Fitri, Euis Nessia; Dewi, Evi Veronica (Jurnal Pajak Populis, 2025)
Extracurricular service units at SMKS Musik Jakarta play an important role in supporting students’ skill development and generating potential income for the school. However, financial management and accounting practices within these service units have not yet been implemented optimally or systematically. This Community Service Program (PKM) aims to enhance the knowledge and skills of extracurricular service unit managers in financial management and basic accounting. The program was implemented through training and mentoring activities, including the delivery of materials, discussions, and hands-on practice in recording financial transactions and preparing simple financial reports. The participants of this program included service unit managers, supervising teachers, and students who are directly involved in managing the service activities. The results indicate an improvement in participants’ understanding of the importance of orderly, transparent, and accountable financial management, as well as their ability to perform simple and structured financial record-keeping. It is expected that this program will enable extracurricular service units at SMKS Musik Jakarta to be managed more professionally and sustainably.